Dynamics of language conflicts in the 21st century - Panasenko, Hanna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
Almost in the first quarter of the third millennium, in many countries of the world, there is a progressive dynamics of linguistic conflicts, which sometimes turn into an armed conflict. Of course, language conflicts have a very long history, but their present is even brighter. At the heart of the language conflict, as is known, is linguistic inequality, which is characterized by the status of language. The subject of the study is the impact of the globalization processes of the twenty-first century. on the development of modern language conflicts and the possibility of their settlement. The goal of the work is to reveal the essence of modern language conflicts, to clarify their peculiarities; the study of the dynamics of linguistic conflicts in the XXI century, the possible development and outline ways to solve them. The objective to analyze the dynamics of linguistic conflicts of the XXI century and to determine their possible development, outlining ways to solve contemporary linguistic conflicts. General scientific methods are used: analysis, synthesis, hypothetical method. The following results are obtained: the process of national self-affirmation, the observance of the language and culture of its legal rights must be developed and implemented by the country’s elite. This process must be constant and steady; the linguistic conflict, however, is an undesirable phenomenon in the life of society, which is a kind of obstacle in solving the problems of the social life of people of all nationalities. Only non-violent method of overcoming linguistic conflicts will lead to harmonization of society. Linguistic conflict can help in this. Conclusions: a "clearing up" and neutralization of linguistic conflicts can be assisted by a sound linguistic policy and concerted efforts to reconcile all the warring parties, seeking consensus, and most importantly, fair determination of the significance of conflicting languages and equalization of the possibilities of realization in all spheres of life.